Rhizoctonia Top Flagging-a Potentially Dangerous New Disease of Pinus kesiya - Mehrotra, M. D. (Indian Forester, 1990)
Top flagging, a highly destructive disease of Pinus kesiya caused by Rhizoctonia solani anamorph of Thanatephorun cucumeris is described for the first time from India. Seedling raised in the beds suffered heavy casualty to the extent of 70-80% following heavy rain. Warm and excessive humid conditions favoured the development of the disease. The disease spread from plant to plant through contact of the foliage. Group dying of seedlings, drooping of top and entangling of top and entangling by fungus hypbae were the characteristic features of the disease. Overcrowdings of seedlings may be avoided in the beds and also the disease seedlings removed as soon as the symptoms of the disease are noticed. This will help in preventing lateral spread of the disease by contact. It has been possible to keep the incidence of the disease under check by raising the seedlings in polypots.